ANALISIS PENYEBARAN SIFAT FISIS BATUAN RESERVOIR DENGAN METODE GEOSTATISTIK (STUDI KASUS: LAPANGAN BOONSVILLE, TEXAS, AMERIKA SERIKAT) - Puspita Sari, Claudia Dewi; Lepong, Piter; Natalisanto, Adrianus Inu (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2019)
Physical properties of reservoir rocks are very important in hydrocarbon production. This study analyzes the physical properties of porosity value in reservoir rocks. The aim was to estimate the distribution of porosity in the reservoir rocks. There are several methods available in estimating the reservoir properties distribution. This study uses the geostatistical method to estimate the distribution of porosity value in three different wells in Boonsville Field. Semivariogram analysis is essential steps in geostatistical method in analysis the autocorrelation the the petrophysical data of geophysical logging. The experimental semivariogram with spherical model obtained the sill value 14,94; nugget value 7,85; and range value 1646. The value use as input data in estimate the distribution of porosity value by ordinary kriging. Result of estimation using geostatistical method shown in around well area of IG Yates 31 and IG Yates 19 have the most optimal physical properties as reservoir rocks.